Effect of selective brain cooling versus core cooling on achieving target temperature among patients with severe traumatic brain injury - Azza Abd Elrazek Baraka; Eman Arafa Hassan; Azza Hamdi El-Soussi; Hany Eid Mohamed (Elsevier, 2020)
Background: Neurotrauma is expected to become the third leading cause of death and disability worldwide. One of these serious injuries is a traumatic brain injury. It is estimated that 10 million people sustain a traumatic brain injury yearly. Aim: To assess the effect of selective brain cooling versus core cooling on achieving target temperature among patients with severe traumatic brain injury. Research hypotheses: Patients subjected to selective brain cooling method exhibit a rapid temperature reduction rate than those subjected to the core cooling method. Patients subjected to selective brain cooling method show early improvement in neurological injury severities than those subjected to the core cooling method. Study design: A quasi-experimental control and study group design was conducted in this study. Method: This study was conducted at Alexandria Main University Hospital namely unit I, unit II, unit III and general ICU at Smouha University Hospital. Subject: A convenience sample of 80 newly admitted patients with severe traumatic brain injury and exhibited a refractory fever were assigned randomly into two equal groups. Results: Regarding cooling methods success in reducing core temperature, selective brain cooling method success in achieving the target temperature was (75.0%) compared to (45.0%) of patients in the core cooling method. Regarding cooling methods success in reducing brain temperature, selective brain cooling success in achieving target temperature is (85.0%) of patients compared to (10%) of patients in the core cooling method. Conclusion: The selective brain cooling method is effective in achieving target temperature than the core cooling method.